Comparison of the Effectiveness of Continuous Positive Airway Pressure (CPAP) Therapy with a Combination of High-Frequency Oscillations and CPAP in the Treatment of Respiratory Distress Syndrome in Infants - Roya Choupani Dastgerdi; Majid Hamidi; Marzieh Khalili Dehkordi; Ahmad shah Farhat (Mashhad University of Medical Sciences, 2022)
Background: Invasive mechanical ventilation in infants suffering from respiratory distress syndrome (RDS) is associated with some complications, such as chronic lung disease, and therefore, the tendency to use non-invasive methods is increasing. The present study aimed to compare the effect of non-invasive continuous positive airway pressure (CPAP) and a combination of high-frequency oscillation ventilation (HFOV) and CPAP in the treatment of RDS in infants.Methods: In this clinical trial, 37 infants suffering from RDS admitted to the Neonatal Intensive Care Unit of Hajar Hospital in Shahrekord were randomly assigned to two groups treated with CPAP alone and CPAP plus HFOV. The baseline information, including gestational age, time of birth, weight, gender, duration of hospitalization, duration of oxygenation and CPAP, the time of transition to oral feeding, and hemodynamic parameters, were recorded. The obtained data were analyzed in Stata software.Results: The mean scores of the length of hospitalization, the time to start and complete oral feeding, as well as the duration of CPAP and oxygenation, were higher in the CPAP group, as compared to those in the HPA+CPAP group; nonetheless, the differences were significant only for the duration of oxygenation (P<0.05).Conclusion: As evidenced by the obtained results, the use of HFOV+CPAP led to a more significant reduction in the duration of oxygen therapy, as compared to CPAP, in preterm neonates suffering from RDS.